Transformation Of Fishermen's Settlements in Manado City: Case Study of Coastal Reclamation Boulevard Dua - Dariwu, Claudia Talita; Pangauw, Kindly Anugerah Imanuel; Pangalila, Fiska Chintya Ezra (Departement of Architecture, Universitas Islam Indonesia, 2026)
Research explores the Transformation of Fishing Settlements in the Boulevard Dua coastal reclamation area of Manado City, focusing on how communities adapt to ecological changes and coastal urbanization. The reclamation initiative, intended to expand urban land, has resulted in shifts in spatial layouts, housing designs, and fishermen's income sources. Utilizing a mixed-methods approach that combines GIS-based spatial analysis, direct field surveys, and in-depth interviews, the study uncovers that settlements now face inland rather than the sea, and traditional homes have transitioned into permanent multifunction residences. Livelihoods have moved from exclusive fishing to services and small-scale commerce. These observations demonstrate social and architectural adaptations to urban development pressures, while emphasizing the importance of fair, environmentally friendly coastal planning centered on local communities. Building on this context, the research explicitly targets three core issues in post-reclamation settlement transformation: spatial patterns of settlement, shifts in housing functions, and alterations in the architectural identity of local communities. The problem scope encompasses changes in spatial orientation from sea to land, reconfiguration of settlements from linear to grid or cluster forms, modifications of house roles from single-purpose to productive dwellings, and the effects on the continuity of coastal architectural identity deeply rooted in maritime culture. The anticipated results will not only chart physical and functional changes but also elucidate how fishing communities formulate adaptation strategies to uphold their architectural and social identities amid challenges posed by urbanization and reclamation policies.